Understanding the Struggle of University Students in Indonesia - Setiawan, Jenny Lukito (Faculty of Psychology, Universitas Surabaya, 2008)
The aim of this study is to describe university students’ concern and its complexity. Partic- ipants were 68 students from two private universities in Indonesia. In order to achieve deep under- standing of the issue, the qualitative approach was adopted. Data were obtained through individual in- terviews and focus group discussions. Results show that problems related to academic, relationships with others, transitions to university, romantic relationships, and self were frequently reported by stu- dents. Academic-related problems were mostly characterised by difficulties in coping with academic demands and difficulties over time management. In regard to problems in romantic relationships, the selection of a partner is a strong issue, which was complicated not only by a lack of social skills to build relationships, but also by parental prohibition from having such relationships before students complete their studies. Self-related problems involve concerns related to self-concept, self-esteem and confidence, uncertainty about values and struggle towards maturity. The interrelations of these issues and the implications for supporting students are further discussed. Tujuan studi ini adalah menguraikan keprihatinan mahasiswa dan kompleksitasnya. Partisi- pan adalah 68 mahasiswa dari dua universitas swasta di Indonesia. Agar diperoleh pengertian yang mendalam, dilakukan pendekatan kualitatif. Data diperoleh melalui wawancara dan diskusi kelompok terpumpun. Hasil menunjukkan bahwa masalah terkait akademik, hubungan dengan orang lain, transi- si ke perguruan tinggi, hubungan romantik, dan masalah pribadi sering dilaporkan para mahasiswa. Masalah terkait akademik terutama dicirikan oleh kesulitan mengatasi tuntutan akademik dan kesuli- tan mengatur waktu. Terkait masalah hubungan romantis, pemilihan pasangan merupakan masalah berat, yang makin rumit bukan hanya karena kelemahan keterampilan sosial untuk membangun hu- bungan, tetapi juga oleh larangan orang tua untuk terlibat hubungan demikian sebelum studi tuntas. Masalah pribadi menyangkut hal-hal terkait konsep-diri, percaya-diri dan keyakinan, ketakpastian tentang nilai dan perjuangan ke arah kematangan. Kesalingterkaitan antar-isu tersebut dan implika- sinya untuk mendukung para mahasiswa dibahas lebih lanjut.